Two new species of Callulina (Amphibia: Anura: Brevicipitidae) from the Nguru Mountains, Tanzania - Loader, Simon P.; Gower, David J.; Müller, Hendrik; Menegon, Michele (Zootaxa, 2010)
Two new species of Callulina are described from the Nguru Mountains, one from the main Nguru South block (C. hanseni sp. nov.) and one from the outlying mountain fragment of the Nguru in Kanga Forest Reserve (C. kanga sp. nov.). The species are diagnosed based on a combination of morphological, acoustic and molecular data. An updated key to the species of all the known Callulina is provided. The conservation status of the two species is examined and, based on highly restricted distributions and ongoing threat to their Nguru Mountain habitats, we recommend a Critically Endangered categorisation. Additional species of Callulina remain to be described from the Nguru Mountains, underlying the extraordinary diversity of the genus in this area.